A molecular-genetic and imaging-genetic approach to specific comprehension difficulties in children. (December 2018) - Li, Miao; Malins, Jeffrey; DeMille, Mellissa; Lovett, Maureen; Truong, Dongnhu; Epstein, Katherine; Lacadie, Cheryl; Mehta, Chintan; Bosson-Heenan, Joan; Gruen, Jeffrey; Frijters, Jan
Abstract Children with poor reading comprehension despite typical word reading skills were examined using neuropsychological, genetic, and neuroimaging data collected from the Genes, Reading and Dyslexia Study of 1432 Hispanic American and African American children. This unexpected poor comprehension was associated with profound deficits in vocabulary, when compared to children with comprehension skills consistent with their word reading. Those with specific comprehension difficulties were also more likely to have RU2Short alleles of READ1 regulatory variants ofDCDC2, strongly associated with reading and language difficulties. Subjects with RU2Short alleles showed stronger resting state functional connectivity between the right insula/inferior frontal gyrus and the right supramarginal gyrus, even after controlling for potentially confounding variables including genetic ancestry and socioeconomic status. This multi-disciplinary approach advances the current understanding of specific reading comprehension difficulties, and suggests the need for interventions that are more appropriately tailored to the specific comprehension deficits of this group of children. Neuroscience: Biology helps explain reading comprehension difficulties Biological data can help us better understand why as many as 15% of children struggle to comprehend what they read even when they are skilled at decoding individual words. An international team of researchers led by Dr. Jeffrey Gruen at Yale University School of Medicine collected behavioral, genetic, and brain imaging data from African American and Hispanic American children with specific difficulties in reading comprehension. These children were found to (1) be more likely to have certain variants of the reading disability risk geneDCDC2, (2) have stronger functional brain connectivity between the right insula/inferior frontal gyrus and the right supramarginal gyrus, and (3) have profound deficits in vocabulary. These multidisciplinary findings deepen our understanding of specific reading comprehension difficulties and pave the way for more effective reading interventions that are tailored to students with these challenges.